Rapid and visually interpretable LAMP assay for detection of pathogenic Pseudomonas aeruginosa in artificial sputum - Shukla Banerjee; Sukesh Kumar Bajire; Adarsh B. Mynalli; Rajesh P. Shastry (Molecular Biology Reports, 2026)

Acetobacter cibinongensis cellulose loaded with 6-Methylcoumarin inhibits Chromobacterium violaceum biofilm - Rajesh P. Shastry; Shukla Banerjee; Sukesh Kumar Bajire (Biocatalysis and Agricultural Biotechnology, 2026)

Emerging Trends in the Climate Change Impact on Indian Summer Monsoon Rainfall - B. N. Goswami; P. V. Rajesh; Subodh K. Saha; Bijit K. Banerjee; Devabrat Sharma (Advances in Atmospheric Sciences, 2026)

Carbon dioxide-fuelled self-propelled anisotropic Nanoflask motors encapsulating polymeric micelles for deep Helicobacter pylori eradication - P.K. Anjana; Sri Ganga Padaga; P S Shishira; Tonmoy Banerjee; Balaram Ghosh; Swati Biswas (Chemical Engineering Journal, 2026)

Quantification and characterization of soil organic carbon with different environmental gradients for the high altitude wetlands of Indian Himalaya - Narayan P. Anugraha; D. Ganguly; A. Paneer Selvam; Kakolee Banerjee; M. Harikrishna Prasad; Lakpa Tamang; Sushmita Chettri; Anupriya Soni; Rajesh Joshi; Ajay Kumar Gupta; Prakash Chhetri; Ramachandran Purvaja (Environmental Geochemistry and Health, 2026)

A Digital Twin Ocean: can we improve coastal ocean forecasts using targeted marine autonomy? - Dale Partridge; Deep Banerjee; David Ford; Ke Wang; Jozef Skákala; Juliane Wihsgott; Prathyush P. Menon; Susan Kay; Daniel Clewley; Andrea Rochner; Emma Sullivan; Matthew Palmer (Ocean Science, 2026)
This study outlines the development and testing of a Digital Twin Ocean (DTO) framework, aimed at improving coastal ocean forecasts through the use of autonomous underwater gliders. A fleet of gliders were deployed in the western English Channel during August-September 2024 to collect measurements of temperature, salinity, chlorophyll and oxygen, aiming to track the movement of the harmful algal bloom Karenia mikimotoi. Measurements were assimilated into a very high resolution (1.5 km) numerical forecast model, with an implementation of biogeochemistry data assimilation for this purpose. The model forecast was then used by a probabilistic uncertainty model to plan a series of waypoints to navigate the glider fleet towards features of interest. By utilising a continuous feedback loop of measurement, prediction, guidance, and refinement a system with real time coupling between the real ocean environment and its digital counterpart has been established. Building upon a prior pilot study of Ford et al. (2022), this work improves every element of the system to address several limitations of the prior configuration. Whilst a bloom was present in the wider area, measurements and modeling suggest it didn't enter the glider operation zone. Despite this and other operational challenges the mission clearly demonstrates the benefits of such a system. The ability to simultaneously track multiple features of interest, namely chlorophyll maxima and oxygen minima, would not have been possible with a single glider resulting in significant benefits to the system. Furthermore, the improvement to biogeochemical forecasting has been demonstrated through a series of post mission experiments, highlighting the advantages of high temporal resolution observations and increased spatial resolution of the model.

Deficient arsenic methylation and global proteomic reprogramming in human keratinocytes during arsenic-induced skin carcinogenesis - Alexandra N. Nail; Mayukh Banerjee; Manting Xu; Caitlin H. Reynolds; Miroslav Stýblo; Peter H. Cable; Daniel W. Wilkey; Michael L. Merchant; Ana P. Ferragut Cardoso; Shelia D. Thomas; J. Christopher States (Archives of Toxicology, 2026)
Chronic inorganic arsenic (iAs) exposure affects > 220 million people worldwide and skin cancer is a hallmark of long-term iAs exposure. Limited information exists regarding arsenic methylation by human keratinocytes and how methylation influences skin carcinogenesis. Inorganic arsenite (iAs III ) and its methylated metabolites disrupt diverse zinc finger proteins, leading to differential toxicity patterns. We examined arsenic methylation capacity in non-malignant human keratinocytes and interrogated proteomic remodeling across three stages of iAs III induced malignant transformation using the well-established preclinical HaCaT model. Arsenic methylation was assessed by hydride generation cryotrapping inductively coupled-mass spectrometry and global proteomic changes were analyzed by tandem-mass tagging liquid chromatography-tandem mass spectrometry. Primary, hTERT-immortalized and HaCaT human keratinocytes exhibited negligible arsenic methylation, with iAs III comprising at least 98.5% of total intracellular arsenic, attributable to minimal expression of arsenite methyltransferase. Proteomic profiling identified over 275 differentially expressed proteins at each stage of transformation, including multiple zinc finger proteins implicated in cell cycle control, RNA metabolism, and genome stability. Ingenuity® Pathway Analysis revealed progressive, coordinated disruption of cancer-associated pathways and regulatory networks over the transformation timeline, including zinc-coordinating upstream regulators that may explain widespread pathway dysregulation. Collectively, our findings suggest that iAs III promotes skin carcinogenesis by disrupting C3H1- and C4-type zinc finger protein-centered regulatory networks that coordinate cancer-associated signaling and metabolic pathways in human keratinocytes, highlighting key candidates for future mechanistic studies.

Multi-level toxicity assessment of sub-lethal mercury exposure in Clarias batrachus - K. Dhara; S. Ghosh; M. Barman; S. Dey; K. Sen; P. Banerjee; N. C. Saha; C. R. Multisanti; S. Saha; C. Faggio (International Journal of Environmental Science and Technology, 2026)

Yield Stability of aus Rice Genotypes Across Contrasting Rainfed Agro-Ecologies: Identifying Potential Donors for Rainfed Rice Improvement - Puranjoy Sar; Umakanta Ngangkham; Koushik Chakraborty; B. C. Verma; Priyamedha; Amrita Banerjee; N. P. Mandal; Somnath Roy (Indian Journal of Genetics and Plant Breeding, 2026)

Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

Chromium propionate supplementation during late gestation in Brangus cows alters offspring growth, physiology, and neonatal hepatic transcriptome - Hiam Marcon; Wellison J.S. Diniz; Matheus F.L. Ferreira; Ashley K. Edwards; Mariana Santos; Joao V. Chinaglia; Gilmara P. Leite; Barbara R. dos Reis; Tristan C. Brown; Priyanka Banerjee; Gustavo R. Siqueira; Marcelo Vedovatto (Animal Feed Science and Technology, 2026)

The Hainan plume and the origin of tectonic and magmatic activity in Southeast Asia - Rupak Banerjee; Chujie Liu; Stephen P. Grand; Eric Sandvol; Supriyo Mitra; Xiaofeng Liang; Shengji Wei (Tectonophysics, 2026)

Mobility of heavy rare earth elements in magmatic-hydrothermal systems: Experimental determination of DyPO4 solubility in supercritical fluids - Debarati Banerjee; Laura E. Waters; Nicole C. Hurtig; Alexander P. Gysi; Daniel Harlov; Chen Zhu; Artaches Migdisov (Chemical Geology, 2026)

Empirical drag coefficients for in-flight volcanic bombs: A novel application of aerospace techniques to volcanic hazards - A. Sork; P. Kreit; D. Banerjee; M. Sellier; B. Kennedy; L. Watson; R. Fitzgerald; F. McIntyre; K. Tsunematsu (Journal of Volcanology and Geothermal Research, 2026)

Molecular Epidemiology of Multi-Drug Resistant E. coli Isolated from Poultry Birds in Six Agroclimatic Zones of West Bengal, India: A Cross-Sectional Study - Md Habib; J. Banerjee; S. Batabyal; P. K. Nanda; A. K. Das; U. K. De; I. Samanta; P. Dandapat; S. Bandyopadhyay (Indian Journal of Microbiology, 2025)

Rare earth elements geochemistry, mineral hosts and recovery potential from Singrauli coalfield, India - P. Gopinathan; Amit Karmakar; Kanishk Kumar Karan; Om Prakash Kumar; Prabal Boral; Sanjay Kumar Thakur; Saroj Kumar; Vivek Singh; Priya Kumari; Arshi Perween; Jyoti Sharma; Abhishek Mahato; et al. (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Comparative study on chemical characteristics of aromatic volatile organic compounds (VOCs) and gene expression in scented and non-scented Rosa Hybrida cultivars - P. R. Jadhav; T. P. Ahammed Shabeer; R. S. Yadav; A. Dhole; R. G. Kale; D. V. S. Raju; B. Ghosh; K. Banerjee; K. V. Prasad; P. G. Kawar (Physiology and Molecular Biology of Plants, 2025)

Associations between airborne crude oil chemicals and neurological symptoms among workers in the gulf long-term follow-up study - Kristen N. Cowan; Emily J. Werder; Kaitlyn G. Lawrence; Richard K. Kwok; Patricia A. Stewart; Mark R. Stenzel; Caroline P. Groth; Tran B. Huynh; Sudipto Banerjee; Gurumurthy Ramachandran; W. Braxton Jackson; Frankie LaPorte; et al. (Science of The Total Environment, 2025)

NdPO4 solubility and aqueous Neodymium speciation in supercritical fluids: An experimental study at 500–700 °C and 1.7 kbar - Debarati Banerjee; Laura E. Waters; Nicole C. Hurtig; Alexander P. Gysi; Daniel Harlov; Chen Zhu; Artaches Migdisov (Geochimica et Cosmochimica Acta, 2025)

Optimizing Rootstock Choice for Enhanced Photosynthetic Efficiency, Antioxidant Activity and Yield of Grapes Under Semi-arid Climate - N. A. Deshmukh; S. R. Takale; N. M. Patil; S. D. Gat; P. H. Nikumbhe; K. Banerjee (Applied Fruit Science, 2025)

Physiology, productivity and grain quality of aromatic rice under organic manure and LCC-based N top dressing by neem-coated urea, nano urea and mustard cake - Mainak Sarkar; Prerona Saha; Mrityunjay Ghosh; Sibajee Banerjee; S. K. Gunri; T. Biswas; P. K. Mani; B. C. Patra; C. K. Kundu (Vegetos, 2025)

Age and origin of the Ngankipari Formation in the Noarlunga and Willunga embayments, southern South Australia - R. P. Bourman; S. Buckman; D. K. Panda; D. Banerjee; C. V. Murray-Wallace; W. Preiss (Australian Journal of Earth Sciences, 2025)

Study of a geodetic NavIC receiver for timing application - Sukabya Dan; P. Banerjee; Rahul Mondal; Anindya Bose; Chaitali Koley; Ashish Agarwal; Mahavir Prasad Olaniya; Suchi Yadav (GPS Solutions, 2025)

Exploring gelatin from Black Bengal and Native Deccani Goat skin: Specialty meat breeds of India - P. Sowmya Reddy; Naveena B. Maheswarappa; G.V. Bhaskar Reddy; Rituparna Banerjee; J. Indumathi; G. Gangaraju; Bidyut Prava Mishra; Gopal Patra (Small Ruminant Research, 2025)

Transformation in energy content of non-coking coals during differential settling beneficiation process: Implications for energy impact - Amit Karmakar; P. Gopinathan; Om Prakash Kumar; Manoj K. Sethi; T. Subramani; M. Santosh; Pradip K. Banerjee (Fuel, 2024)

Amorphous carbon nanotubes as a potent remover of textile dyes: methylene blue and malachite green - D. Banerjee; N. Garg; K. Chauhan; M. Parashar; P. Kumar (Nanotechnology for Environmental Engineering, 2024)

Loop-mediated isothermal amplification (LAMP) assay for early on-site detection of Group B Streptococcus infection in neonatal sepsis blood sample - Shukla Banerjee; Mithun H. K.; Rajesh P. Shastry (Molecular Biology Reports, 2024)

Genome-wide association study identified QTLs and genes underlying early seedling vigour in aus rice (Oryza sativa L.) - Firos T. M. Basha; Puranjoy Sar; Prolay K. Bhowmick; Anima Mahato; Deepak S. Bisht; Mir A. Iquebal; Koushik Chakraborty; Amrita Banerjee; Bibhash C. Verma; Debarati Bhaduri; Jitendra Kumar; Umakanta Ngangkham; et al. (Molecular Genetics and Genomics, 2024)

Every Day Counts- a Randomized Nutrition and Physical Activity Pilot Intervention for Women with Metastatic Breast Cancer - S. Contreras; P. Sheean; L. Matthews; A. Visotcky; A. Banerjee; A. Moosreiner; K. Kelley; C. Chitambar; P. Papanek; M. Stolley (Journal of the Academy of Nutrition and Dietetics, 2024)

Egg Yolk Lecithin as a Dietary Supplement in Juvenile Silver Pompano, Trachinotus blochii: Effects on Growth and Health Parameters - Meenu Devassykutty; Boby Ignatius; P. Vijayagopal; Sanal Ebeneezar; Paramita Banerjee Sawant; A. M. Babitha Rani; Eldho Varghese; P. Sayooj; K A Sajina (Thalassas: An International Journal of Marine Sciences, 2024)

A high-resolution seismic velocity model for East Asia using full-waveform tomography: Constraints on India-Asia collisional tectonics - Chujie Liu; Rupak Banerjee; Stephen P. Grand; Eric Sandvol; Supriyo Mitra; Xiaofeng Liang; Shengji Wei (Earth and Planetary Science Letters, 2024)

MITOCHONDRIAL DEFECTS IN THE PARL-DEFICIENT MOUSE MODEL LEAD TO ARRESTED SPERMATOGENESIS AND FERROPTOSIS - E. Radaelli; C.A. Assenmacher; J. Verrelle; E. Banerjee; F. Manero; S. Khiati; A. Girona; G. Lopez-Lluch; P. Navas; M. Spinazzi (Journal of Comparative Pathology, 2024)

Chronic arsenic exposure suppresses proteasomal and autophagic protein degradation - Isabell I. Augenstein; Alexandra N. Nail; Ana P. Ferragut Cardoso; J. Christopher States; Mayukh Banerjee (Environmental Toxicology and Pharmacology, 2024)

Halophyte and bivalve-based integrated multi-trophic aquaculture (IMTA): effect on growth, water quality, digestive and antioxidant enzymes of Penaeus monodon and Chanos chanos reared in brackishwater ponds - Rathod Kumara; Karthireddy Syamala; P. S. Shyne Anand; N. K. Chadha; Paramita Banerjee Sawant; Pooja Chithira; A. P. Muralidhar (Aquaculture International, 2024)

Tsunami or storm? A high-level coastal boulder field on the southern tip of Eyre Peninsula, South Australia - R. P. Bourman; C. V. Murray-Wallace; D. Panda; S. Buckman; D. Banerjee; D. D. Ryan; L. T. White (Australian Journal of Earth Sciences, 2024)

Practical Guide to Measuring Wetland Carbon Pools and Fluxes - Sheel Bansal; Irena F. Creed; Brian A. Tangen; Scott D. Bridgham; Ankur R. Desai; Ken W. Krauss; Scott C. Neubauer; Gregory B. Noe; Donald O. Rosenberry; Carl Trettin; Kimberly P. Wickland; Scott T. Allen; et al. (Wetlands, 2023)
Wetlands cover a small portion of the world, but have disproportionate influence on global carbon (C) sequestration, carbon dioxide and methane emissions, and aquatic C fluxes. However, the underlying biogeochemical processes that affect wetland C pools and fluxes are complex and dynamic, making measurements of wetland C challenging. Over decades of research, many observational, experimental, and analytical approaches have been developed to understand and quantify pools and fluxes of wetland C. Sampling approaches range in their representation of wetland C from short to long timeframes and local to landscape spatial scales. This review summarizes common and cutting-edge methodological approaches for quantifying wetland C pools and fluxes. We first define each of the major C pools and fluxes and provide rationale for their importance to wetland C dynamics. For each approach, we clarify what component of wetland C is measured and its spatial and temporal representativeness and constraints. We describe practical considerations for each approach, such as where and when an approach is typically used, who can conduct the measurements (expertise, training requirements), and how approaches are conducted, including considerations on equipment complexity and costs. Finally, we review key covariates and ancillary measurements that enhance the interpretation of findings and facilitate model development. The protocols that we describe to measure soil, water, vegetation, and gases are also relevant for related disciplines such as ecology. Improved quality and consistency of data collection and reporting across studies will help reduce global uncertainties and develop management strategies to use wetlands as nature-based climate solutions.

Clonal variability in chromosomal instability as a potential driver in the acquisition of tumorigenic phenotype in chronic arsenic-exposed and hsa-miR-186 overexpressing human keratinocytes - Angeliki Lykoudi; Ana P. Ferragut Cardoso; Sandra S. Wise; Mayukh Banerjee; J. Christopher States (Toxicology and Applied Pharmacology, 2023)

Satellite Epidemic of Covid-19 Associated Mucormycosis in India: A Multi-Site Observational Study - Aanchal Satija; Tanu Anand; Aparna Mukherjee; Poonam Sharma Velamuri; Kh. Jitenkumar Singh; Madhuchhanda Das; Kripa Josten; Archana Y. Keche; Nitin M. Nagarkar; Prashant Gupta; D. Himanshu; Sejal N. Mistry; et al. (Mycopathologia, 2023)

Influence of dietary microalgal concentrates on growth, survival and health status of Penaeus vannamei - K. P. Sandeep; T. Sivaramakrishnan; S. Sudhin; J. A. J. Raymond; N. S. Sudheer; R. Ananda Raja; Sujeet Kumar; J. Syama Dayal; C. P. Balasubramanian; Paramita Banerjee Sawant; N. K. Chadha; K. Ambasankar (Aquaculture International, 2023)

CEC01-02 (B): A hands-on introduction to applied artificial intelligence in toxicology: Advanced Deep Learning for Toxicology - P. Banerjee (Toxicology Letters, 2023)

3-(Bromoacetyl) coumarin is a potential therapeutic agent against neonatal sepsis-associated Pseudomonas extremorientalis - Shukla Banerjee; Sukesh Kumar Bajire; H. K. Mithun; Rajesh P. Shastry (Archives of Microbiology, 2023)

Exposure to volatile hydrocarbons and neurologic function among oil spill workers up to 6 years after the Deepwater Horizon disaster - Dazhe Chen; Emily J. Werder; Patricia A. Stewart; Mark R. Stenzel; Fredric E. Gerr; Kaitlyn G. Lawrence; Caroline P. Groth; Tran B. Huynh; Gurumurthy Ramachandran; Sudipto Banerjee; W. Braxton Jackson II; Kate Christenbury; et al. (Environmental Research, 2023)

RNA Sequencing of Intraoperative Peritumoral Tissues Reveals Potential Pathways Involved in Glioma-Related Seizures - Krishan Kumar; Vivek Dubey; Syeda S. Zaidi; Manjari Tripathi; Fouzia Siraj; Mehar Chand Sharma; P. Sarat Chandra; Ramesh Doddamani; Aparna Banerjee Dixit; Jyotirmoy Banerjee (Journal of Molecular Neuroscience, 2023)

Search for CP violation and measurement of branching fractions and decay asymmetry parameters for Λ c + → Λ h + and Λ c + → Σ 0 h + ( h = K , π ) - L.K. Li; W. Shan; K. Kinoshita; I. Adachi; H. Aihara; D.M. Asner; H. Atmacan; T. Aushev; V. Babu; S. Bahinipati; Sw. Banerjee; P. Behera; et al. (Science Bulletin, 2023)

Purification of domestic laundry wastewater in an integrated treatment system consists of coagulation and ultrafiltration membrane process - S. Vishali; E. Poonguzhali; Indhurekha Banerjee; Sharan Sakshi George; P. Srinivasan (Chemosphere, 2023)

Fine particulate matter and incident coronary heart disease events up to 10 years of follow-up among Deepwater Horizon oil spill workers - Dazhe Chen; Dale P. Sandler; Alexander P. Keil; Gerardo Heiss; Eric A. Whitsel; Gregory C. Pratt; Patricia A. Stewart; Mark R. Stenzel; Caroline P. Groth; Sudipto Banerjee; Tran B. Huynh; Jessie K. Edwards; et al. (Environmental Research, 2023)

Paleodepositional and Hydrocarbon Source-Rock Characteristics of the Sonari Succession (Paleocene), Barmer Basin, NW India: Implications from Petrography and Geochemistry - Vikram P. Singh; Bhagwan D. Singh; Runcie P. Mathews; Alpana Singh; Vinod A. Mendhe; Subhashree Mishra; Mollika Banerjee (Natural Resources Research, 2022)

Transcriptomic profiling of nonneoplastic cortical tissues reveals epileptogenic mechanisms in dysembryoplastic neuroepithelial tumors - Krishan Kumar; Aparna Banerjee Dixit; Manjari Tripathi; Vivek Dubey; Fouzia Siraj; Mehar Chand Sharma; Sanjeev Lalwani; P Sarat Chandra; Jyotirmoy Banerjee (Functional & Integrative Genomics, 2022)

An Early Season Perspective of Key Differentially Expressed Genes and Single Nucleotide Polymorphisms Involved in Sucrose Accumulation in Sugarcane - Nandita Banerjee; Sanjeev Kumar; A. Annadurai; Alok Singh; P. K. Singh; J. Singh; R. K. Singh; Sanjeev Kumar (Tropical Plant Biology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Identification of potential MTAs and candidate genes for juice quality- and yield-related traits in Saccharum clones: a genome-wide association and comparative genomic study - Shanmugavel Senthilkumar; K. K. Vinod; Selvaraj Parthiban; Prathima Thirugnanasambandam; Thalambedu Lakshmi Pathy; Nandita Banerjee; Thelakat Sasikumar Sarath Padmanabhan; P. Govindaraj (Molecular Genetics and Genomics, 2022)

Biochemical, molecular and in silico characterization of arsenate reductase from Bacillus thuringiensis KPWP1 tolerant to salt, arsenic and a wide range of pH - Paromita Banerjee; Ananya Chatterjee; Sushmita Jha; Nirbhay K. Bhadani; Partha P. Datta; Tapas K. Sengupta (Archives of Microbiology, 2022)

Temperature over the Himalayan foothill state of Uttarakhand: Present and future - Arkadeb Banerjee; A P Dimri; K Kumar (Journal of Earth System Science, 2021)

Are ocean-moored buoys redundant for prediction of Indian monsoon? - Maheswar Pradhan; Ankur Srivastava; Suryachandra A. Rao; Deep Sankar Banerjee; Abhisek Chatterjee; P. A. Francis; O. P. Sreejith; M. Das Gupta; V. S. Prasad (Meteorology and Atmospheric Physics, 2021)

Fabrication and development of a thorax phantom to evaluate 3D CRT treatment planning techniques for post-mastectomy chest wall radiotherapy - Dilson Lobo; Srinivas Challapalli; Sourjya Banerjee; Suman Kumar Putha; P. U. Prakash Saxena; Raghavendra Holla; R. Shreyas; Ravichandran Ramamoorthy (Physical and Engineering Sciences in Medicine, 2021)

Rainfall over the Himalayan foot-hill region: Present and future - Arkadeb Banerjee; A P Dimri; Kireet Kumar (Journal of Earth System Science, 2020)

Host-delivered RNA interference in tomato for mediating resistance against Meloidogyne incognita and Tomato leaf curl virus - Ramanna Koulagi; Sagar Banerjee; Bharat H. Gawade; Ashish Kumar Singh; P. K. Jain; Shelly Praveen; K. Subramaniam; Anil Sirohi (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Luminescence dating of Quaternary alluvial successions, Sellicks Creek, South Mount Lofty Ranges, southern Australia - R. P. Bourman; D. Banerjee; C. V. Murray-Wallace; S. Buckman; D. K. Panda; A. P. Belperio; C. L. Jayawardena (Australian Journal of Earth Sciences, 2020)

UAV-hyperspectral imaging of spectrally complex environments - Bikram Pratap Banerjee; Simit Raval; P. J. Cullen (International Journal of Remote Sensing, 2020)

A Review on Basic Biology of Bacterial Biofilm Infections and Their Treatments by Nanotechnology-Based Approaches - Debjani Banerjee; P. M. Shivapriya; Pavan Kumar Gautam; Krishna Misra; Amaresh Kumar Sahoo; Sintu Kumar Samanta (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Assessment of vegetation under air pollution stress in urban industrial area for greenbelt development - S. Banerjee; A. Banerjee; D. Palit; P. Roy (International Journal of Environmental Science and Technology, 2019)

Candidate screening of blast resistance donors for rice breeding - Manoj Kumar Yadav; S. Aravindan; U. Ngangkham; S. R. Prabhukarthikeyan; U. Keerthana; S. Raghu; D. Pramesh; A. Banerjee; S. Roy; P. Sanghamitra; T. Adak; Priyanka Priyadarshinee; et al. (Journal of Genetics, 2019)

Comparative analysis of two rainfall retrieval algorithms during extreme rainfall event: a case study on cloudburst, 2010 over Ladakh (Leh), Jammu and Kashmir - Arkadeb Banerjee; A. P. Dimri (Natural Hazards, 2019)

Generation of common coefficients to estimate global solar radiation over different locations of India - Suman Samanta; Pulak Kumar Patra; Saon Banerjee; Lakshmi Narsimhaiah; M. A. Sarath Chandran; P. Vijaya Kumar; Sanjib Bandyopadhyay (Theoretical and Applied Climatology, 2019)

Assessment of resistance to rice tungro disease in popular rice varieties in India by introgression of a transgene against Rice tungro bacilliform virus - G. Kumar; M. Jyothsna; P. Valarmathi; S. Roy; A. Banerjee; J. Tarafdar; B. K. Senapati; S. Robin; S. Manonmani; R. Rabindran; I. Dasgupta (Archives of Virology, 2019)

Beneficial effects of fenofibrate in pulmonary hypertension in rats - Palak Galhotra; Pankaj Prabhakar; Himanshu Meghwani; Soheb A. Mohammed; Sanjay Kumar Banerjee; Sandeep Seth; Milind P. Hote; K. H. Reeta; Ruma Ray; Subir Kumar Maulik (Molecular and Cellular Biochemistry, 2018)

DNA binding, cleavage and cytotoxicity studies of three mononuclear Cu(II) chloro-complexes containing N–S donor Schiff base ligands - Sidhali U. Parsekar; Joseph Fernandes; Arnab Banerjee; Om Prakash Chouhan; Sumit Biswas; Manohar Singh; Durga P. Mishra; Manjuri Kumar (JBIC Journal of Biological Inorganic Chemistry, 2018)

Low Levels of Prohibitin in Substantia Nigra Makes Dopaminergic Neurons Vulnerable in Parkinson’s Disease - Debashis Dutta; Nilufar Ali; Emili Banerjee; Raghavendra Singh; Amit Naskar; Ramesh Kumar Paidi; Kochupurackal P Mohanakumar (Molecular Neurobiology, 2018)

A molecular analysis of selected marine fishes from the southwest coast of India for species delineation - C. Lavina-Vincent; Supriya Dutta; Gaurav Banerjee; R. Saravanan; V. Sachithanandam; P. Krishnan (Marine Biodiversity, 2017)

Identification of marker-trait associations for morphological descriptors and yield component traits in sugarcane - Archana Siraree; Nandita Banerjee; Sanjeev Kumar; M. S. Khan; P. K. Singh; Sanjeev Kumar; Swati Sharma; R. K. Singh; Jyotsnendra Singh (Physiology and Molecular Biology of Plants, 2017)

Trend and variability of atmospheric ozone over middle Indo-Gangetic Plain: impacts of seasonality and precursor gases - K. Shukla; Prashant K. Srivastava; T. Banerjee; Viney P. Aneja (Environmental Science and Pollution Research, 2017)

Mineral chemistry of tourmaline from Mashak Pahar, South Purulia Shear Zone (SPSZ), eastern Indian Shield - SANTANU ACHARJEE; JYOTISANKAR RAY; PAYEL DEY; DEBAPRIYA BHATTACHARYYA; MOUSUMI BANERJEE; BASAB CHATTOPADHYAY; SHYAMAL SENGUPTA; A K BHATT; D CHOWDHURY; A K DWIVEDI; SANJOY MAHATO; ARKA RANJAN JANA; et al. (Journal of Earth System Science, 2016)

Erratum to: Evaluation of rainfall and wetland water area variability at Thirlmere Lakes using Landsat time-series data - B. P. Banerjee; S. Raval; W. Timms (International Journal of Environmental Science and Technology, 2016)

Evaluation of Ascorbic Acid and Sodium Metabisulfite Applications for Improvement in Raisin Quality - Ajay Kumar Sharma; K. Banerjee; S. D. Ramteke; Satisha Jogaiah; R. G. Somkuwar; P. G. Adsule (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

Desiccation stress induces developmental heterochrony in Drosophila melanogaster - Leena Thorat; Dasharath P Oulkar; Kaushik Banerjee; Bimalendu B Nath (Journal of Biosciences, 2016)

Evaluation of rainfall and wetland water area variability at Thirlmere Lakes using Landsat time-series data - B. P. Banerjee; S. Raval; W. Timms (International Journal of Environmental Science and Technology, 2016)

High genetic diversity and distribution of Bubu-DQA alleles in swamp buffaloes (Bubalus bubalis carabanesis): identification of new Bubu-DQA loci and haplotypes - S. K. Mishra; S. K. Niranjan; B. Banerjee; P. K. Dubey; D. S. Gonge; B. P. Mishra; R. S. Kataria (Immunogenetics, 2016)

Safety Assessment and Bioefficacy of Fluopyram 20 %+Tebuconazole 20 %-40 SC in Chilli, Capsicum annum L. Against Anthracnose Disease - Sujoy Saha; Manjusha R. Jadhav; T. P. Ahammed Shabeer; Kaushik Banerjee; Bineet K. Sharma; M. Loganathan; A. B. Rai (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

Effect of biofilm on water quality and growth of Etroplus suratensis (Bloch, 1790) - M. T. Shilta; Narinder Kumar Chadha; P. K. Pandey; Paramita Banerjee Sawant (Aquaculture International, 2016)

Effect of Low-Intensity Microwave Radiation on Monoamine Neurotransmitters and Their Key Regulating Enzymes in Rat Brain - Kanu Megha; Pravin S. Deshmukh; Alok K. Ravi; Ashok K. Tripathi; Mahesh P. Abegaonkar; Basu D. Banerjee (Cell Biochemistry and Biophysics, 2015)

Practical NK cell phenotyping and variability in healthy adults - Laura S. Angelo; Pinaki P. Banerjee; Linda Monaco-Shawver; Joshua B. Rosen; George Makedonas; Lisa R. Forbes; Emily M. Mace; Jordan S. Orange (Immunologic Research, 2015)

Adsorption–desorption and leaching behavior of kresoxim-methyl in different soils of India: kinetics and thermodynamic studies - Rupali P. Sabale; Ahammed Shabeer T.P.; Soma Dasgupta; Sagar C. Utture; Kaushik Banerjee; Dasharath P. Oulkar; Pandurang G. Adsule; Madhukar B. Deshmukh (Environmental Monitoring and Assessment, 2015)

Controlled Porosity Solubility Modulated Osmotic Pump Tablets of Gliclazide - Arti Banerjee; P. R. P. Verma; Subhash Gore (AAPS PharmSciTech, 2015)

Food and Feeding Ecology of the Non-native Nile Tilapia Oreochromis niloticus (Linnaeus, 1758) in the River Yamuna, India - Absar Alam; N. K. Chadha; K. D. Joshi; S. K. Chakraborty; Paramita Banerjee Sawant; Tarkeshwar Kumar; Kalpana Srivastava; S. C. S. Das; A. P. Sharma (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

Dissipation pattern, safety evaluation, and generation of processing factor (PF) for pyraclostrobin and metiram residues in grapes during raisin preparation - Ahammed Shabeer T. P.; Rushali Girame; Sandip Hingmire; Kaushik Banerjee; Ajay Kumar Sharma; Dasharath Oulkar; Sagar Utture; Manjusha Jadhav (Environmental Monitoring and Assessment, 2015)

Study of impact on surface water and groundwater around flow fields due to changes in river stage using groundwater modeling system - P. K. Roy; S. S. Roy; A. Giri; G. Banerjee; A. Majumder; A. Mazumdar (Clean Technologies and Environmental Policy, 2015)

Kinetics of degradation of carbendazim by B. subtilis strains: possibility of in situ detoxification - Varsha P. Salunkhe; Indu S. Sawant; Kaushik Banerjee; Pallavi N. Wadkar; Sanjay D. Sawant; Sandip A. Hingmire (Environmental Monitoring and Assessment, 2014)

Effect of some climatic parameters on tropospheric and total ozone column over Alipore (22.52 ∘ N, 88.33 ∘ E), India - P K Jana; S Bhattacharyya; A Banerjee (Journal of Earth System Science, 2014)

Conserved C-terminal nascent peptide binding domain of HYPK facilitates its chaperone-like activity - Swasti Raychaudhuri; Rachana Banerjee; Subhasish Mukhopadhyay; Nitai P Bhattacharyya (Journal of Biosciences, 2014)

Pattern of mating preference of interspecific hybrid females and phylogeny in the Drosophila bipectinata species complex - P. BANERJEE; B. N. SINGH (Journal of Genetics, 2014)

Contemporary deformation in the Kashmir–Himachal, Garhwal and Kumaon Himalaya: significant insights from 1995–2008 GPS time series - Sridevi Jade; Malay Mukul; V. K. Gaur; Kireet Kumar; T. S. Shrungeshwar; G. S. Satyal; Rakesh Kumar Dumka; Saigeetha Jagannathan; M. B. Ananda; P. Dileep Kumar; Souvik Banerjee (Journal of Geodesy, 2014)

In toto differentiation of human amniotic membrane towards the Schwann cell lineage - Asmita Banerjee; Sylvia Nürnberger; Simone Hennerbichler; Sabrina Riedl; Christina M. A. P. Schuh; Ara Hacobian; Andreas Teuschl; Johann Eibl; Heinz Redl; Susanne Wolbank (Cell and Tissue Banking, 2014)

Organogenesis and plant regeneration in Zephyranthes rosea Lindl.: Histological and chromosomal study - A. Mujib; S. Banerjee; M. Maqsood; P. D. Ghosh (Plant Biosystems, 2014)

Dissipation kinetics, safety evaluation, and assessment of pre-harvest interval (PHI) and processing factor for kresoxim methyl residues in grape - Rupali Sabale; T. P. Ahammed Shabeer; Sagar C. Utture; Kaushik Banerjee; Manjusha R. Jadhav; Dasharath P. Oulkar; Pandurang G. Adsule; Madhukar B. Deshmukh (Environmental Monitoring and Assessment, 2014)

Commercial steel wool for reduction of hexavalent chromium in wastewater: batch kinetic studies and rate model - P. Mitra; P. Banerjee; D. Sarkar; S. Chakrabarti (International Journal of Environmental Science and Technology, 2014)

Lack of association of Lysyl oxidase (LOX) gene polymorphisms with intracranial aneurysm in a south Indian population - Sanish Sathyan; Linda Koshy; K. R. Sarada Lekshmi; H. V. Easwer; S. Premkumar; Jacob P. Alapatt; Suresh Nair; R. N. Bhattacharya; Moinak Banerjee (Molecular Biology Reports, 2013)

Exploring the relationship between local institutions in SAT India and adaptation to climate variability - Rupsha Banerjee; Josey Kamanda; Cynthia Bantilan; Naveen P. Singh (Natural Hazards, 2013)

Anti-leukemic activity of sulfonoquinovosyldiacylglyceride (SQDG): a constituent of Azadirachta indica leaves - Bharitkar Yogesh P; Shamik Bhattacharya; Tanaya Das; Moumita Roy; Shila E. Besra; Aparna Gomes; Nirup B. Mondal; Sukdeb Banerjee (Medicinal Chemistry Research, 2013)

New antiepileptic agents: structure–activity relationships - Pooja S. Banerjee; P. K. Sharma (Medicinal Chemistry Research, 2012)

Persistence and Dissipation Kinetics of Deltamethrin on Chili in Different Agro-Climatic Zones of India - Suneet Pandher; S. K. Sahoo; R. S. Battu; Balwinder Singh; M. S. Saiyad; A. R. Patel; P. G. Shah; C. Narendra Reddy; D. Jagdishwar Reddy; K. Narasimha Reddy; Ch. Sreenivasa Rao; Tirthankar Banerjee; et al. (Bulletin of Environmental Contamination and Toxicology, 2012)

Development of SSR markers and construction of a linkage map in jute - MOUMITA DAS; SUMANA BANERJEE; RAMAN DHARIWAL; SHAILENDRA VYAS; REYAZUL R. MIR; NILADRI TOPDAR; AVIJIT KUNDU; JITENDRA P. KHURANA; AKHILESH K. TYAGI; DEBABRATA SARKAR; MOHIT K. SINHA; HARINDRA S. BALYAN; et al. (Journal of Genetics, 2012)

Arsenic removal from water using calcined Mg–Al layered double hydroxide - Mridul Chetia; Rajib L. Goswamee; Saumen Banerjee; Soumya Chatterjee; Lokendra Singh; Ravi B. Srivastava; Hari P. Sarma (Clean Technologies and Environmental Policy, 2012)

Crustal Configuration of the Northwest Himalaya Based on Modeling of Gravity Data - Ashutosh Chamoli; Anand K. Pandey; V. P. Dimri; P. Banerjee (Pure and Applied Geophysics, 2011)

Groundwater arsenic contamination in Brahmaputra river basin: a water quality assessment in Golaghat (Assam), India - Mridul Chetia; Soumya Chatterjee; Saumen Banerjee; Manash J. Nath; Lokendra Singh; Ravi B. Srivastava; Hari P. Sarma (Environmental Monitoring and Assessment, 2011)

Probing the structure of human glucose transporter 2 and analysis of protein ligand interactions - Srikanth Duddela; P. Nataraj Sekhar; G. V. Padmavati; Amit Kumar Banerjee; U. S. N. Murty (Medicinal Chemistry Research, 2010)

Persistence and safety risk assessment of propineb in Indian tea - Hemanta Banerjee; P. Ganguly; S. Roy; Devottam Banerjee; M. Paramasivam; Tirthankar Banerjee; K. K. Sharma (Environmental Monitoring and Assessment, 2010)

Age and origin of alluvial sediments within and flanking the Mt Lofty Ranges, southern South Australia: a Late Quaternary archive of climate and environmental change - R. P. Bourman; J. R. Prescott; D. Banerjee; N. F. Alley; S. Buckman (Australian Journal of Earth Sciences, 2010)

The epidemiology of fasciolosis in ruminants in different geo-climatic regions of north India - Rajat Garg; C. L. Yadav; R. R. Kumar; P. S. Banerjee; Stuti Vatsya; Rajesh Godara (Tropical Animal Health and Production, 2009)

Analysis of genetic architecture for some physiological characters in sesame (Sesamum indicum L.) - P. P. Banerjee; P. C. Kole (Euphytica, 2009)

Proctolaclaps regalis usages Drosophila eggs and pupae as ovipositional substrate and their lifecycle closely mimics the life cycle of Drosophila - P. Chatterjee; S. Banerjee; R. N. Chatterjee (Proceedings of the Zoological Society, 2009)

Sorption Behaviour of Forchlorfenuron in Soil - Kaushik Banerjee; Dasharath P. Oulkar; Sangram H. Patil; Soma Dasgupta; Archana T. Nikam; Pandurang G. Adsule (Bulletin of Environmental Contamination and Toxicology, 2008)

Bayesian areal wombling via adjacency modeling - Haolan Lu; Cavan S. Reilly; Sudipto Banerjee; Bradley P. Carlin (Environmental and Ecological Statistics, 2007)

Impact of Doppler Radar Wind in Simulating the Intensity and Propagation of Rainbands Associated with Mesoscale Convective Complexes Using MM5-3DVAR System - S. Abhilash; Someshwar Das; S. R. Kalsi; M. Das Gupta; K. Mohankumar; John P. George; S. K. Banerjee; S. B. Thampi; D. Pradhan (Pure and Applied Geophysics, 2007)

Duration of Anthelmintic Effect of Three Formulations of Ivermectin (Oral, Injectable and Pour-on) Against Multiple Anthelmintic-Resistant Haemonchus contortus in Sheep - R. Garg; R. R. Kumar; C. L. Yadav; P. S. Banerjee (Veterinary Research Communications, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Assimilation of Doppler weather radar observations in a mesoscale model for the prediction of rainfall associated with mesoscale convective systems - S. Abhilash; Someshwar Das; S. R. Kalsi; M. Das Gupta; K. Mohankumar; J. P. George; S. K. Banerjee; S. B. Thampi; D. Pradhan (Journal of Earth System Science, 2007)

Agrobacterium rhizogenes-mediated transformation of Picrorhiza kurroa Royle ex Benth.: establishment and selection of superior hairy root clone - Praveen Chandra Verma; Laiq ur Rahman; Arvind Singh Negi; Dharm Chand Jain; S. P. S. Khanuja; Suchitra Banerjee (Plant Biotechnology Reports, 2007)

Predominance of hepatitis B virus genotype C among Karens, the ‘old settlers’ of Andaman and Nicobar Islands, India - S. Datta; P. K. Chandra; A. Banerjee; R. Chakravarty; K. M. Murhekar; M. V. Murhekar (Archives of Virology, 2007)

Structural studies of a new acidic polysaccharide of apricot seeds - P. N. Banerjee; S. Bhatt (Natural Product Research, 2007)

Effect of adenoviral mediated overexpression of fibromodulin on human dermal fibroblasts and scar formation in full-thickness incisional wounds - Alexander Stoff; Angel A. Rivera; J. Michael Mathis; Steven T. Moore; N. S. Banerjee; Maaike Everts; Antonio Espinosa-de-los-Monteros; Zdenek Novak; Luis O. Vasconez; Thomas R. Broker; Dirk F. Richter; Dale Feldman; et al. (Journal of Molecular Medicine, 2007)

Stable isotope ratios and nodular limestone of the Proterozoic Rohtas Limestone: Vindhyan basin, India - Santanu Banerjee; S. Jeevankumar; P. Sanyal; S. K. Bhattacharyya (Carbonates and Evaporites, 2006)

Immune response to n-terminal and c-terminal deletion mutants of Aspergillus fumigatus major allergen ASP F 3 - Bhanu P. Singh; Banani Banerjee; Puspanita Naik; Jordan N. Fink; Viswanath P. Kurup (Indian Journal of Clinical Biochemistry, 2006)

Dynamics of Organic Carbon and Microbial Biomass in Alluvial Soil With Tillage and Amendments in Rice-wheat Systems - B. Banerjee; P. K. Aggarwal; H. Pathak; A. K. Singh; A. Chaudhary (Environmental Monitoring and Assessment, 2006)

Banned Organochlorine Cyclodiene Pesticide in Ground Water in Varanasi, India - S. K. Singh; P. Raha; H. Banerjee (Bulletin of Environmental Contamination and Toxicology, 2006)

High energy X-γ ray spectrometer on the Chandrayaan-1 mission to the Moon - J. N. Goswami; D. Banerjee; N. Bhandari; M. Shanmugam; Y. B. Acharya; D. V. Subhedar; M. R. Sharma; C. N. Umapathy; P. Sreekumar; M. Sudhakar; L. Abraham; P. C. Agrawal (Journal of Earth System Science, 2005)

Antioxidant activities of seabuckthorn (Hippophae rhamnoides) during hypoxia induced oxidative stress in glial cells - S. Narayanan; D. Ruma; B. Gitika; S. K. Sharma; T. Pauline; M. Sai Ram; G. Ilavazhagan; R. C. Sawhney; D. Kumar; P. K. Banerjee (Molecular and Cellular Biochemistry, 2005)

Immunomodulatory effects of seabuckthorn (Hippophae rhamnoides L.) against chromium (VI) induced immunosuppression - S. Geetha; Vandana Singh; M. Sai Ram; G. Ilavazhagan; P. K. Banerjee; R. C. Sawhney (Molecular and Cellular Biochemistry, 2005)

Metabolism of Fenazaquin, an Acaricide in Tea Plant - J. Bhattacharyya; H. Banerjee; S. P. Das; A. Bhattacharyya (Bulletin of Environmental Contamination and Toxicology, 2005)

Cytoprotective and antioxidant activity of Rhodiola imbricata against tert-butyl hydroperoxide induced oxidative injury in U-937 human macrophages - Kanupriya; D. Prasad; M. Sai Ram; R. Kumar; R. C. Sawhney; S. K. Sharma; G. Ilavazhagan; D. Kumar; P. K. Banerjee (Molecular and Cellular Biochemistry, 2005)

Characterisation of Midgut Antigens of Hyalomma anatolicum anatolicum Koch, 1844 (Acari: Ixodidae) - Rajender Kumar; D. P. Banerjee; P. P. Sengupta (International Journal of Tropical Insect Science, 2002)

SNPs in putative regulatory regions identified by human mouse comparative sequencing and transcription factor binding site data - Poulabi Banerjee; Melanie Bahlo; Jody R. Schwartz; Gabriela G. Loots; Kathryn A. Houston; Inna Dubchak; Terence P. Speed; Edward M. Rubin (Mammalian Genome, 2002)

Effects of dicyandiamide, farmyard manure and irrigation on crop yields and ammonia volatilization from an alluvial soil under a rice ( Oryza sativa L.)-wheat ( Triticum aestivum L.) cropping system - Banerjee B.; Pathak H.; Aggarwal P. (Biology and Fertility of Soils, 2002)

Genomic structures and population histories of linguistically distinct tribal groups of India - Susanta Roychoudhury; Sangita Roy; Analabha Basu; Rajat Banerjee; H. Vishwanathan; M. Usha Rani; Samir K. Sil; Mitashree Mitra; Partha P. Majumder (Human Genetics, 2001)

Evaluation of Adverse Effect of Emisan-6 on Male Albino Rats - S. C. Thakur; S. S. Thakur; S. Banerjee; S. P. Singh (Bulletin of Environmental Contamination and Toxicology, 2001)

Reconstruction of the late Quaternary environment of the lower Luni Plains, Thar Desert, India - A. Kar; A. K. Singhvi; S. N. Rajaguru; N. Juyal; J. V. Thomas; D. Banerjee; R. P. Dhir (Journal of Quaternary Science, 2001)

Molecular biology and immunology of fungal allergens - Viswanath P. Kurup; Banani Banerjee; Kevin J. Kelly; Jordan N. Fink (Indian Journal of Clinical Biochemistry, 2000)

Characterization and some reaction-engineering aspects of thermostable extracellular β-galactosidase from a newBacillus species - R. K. Sani; S. Chakraborti; R. C. Sobti; P. R. Patnaik; U. C. Banerjee (Folia Microbiologica, 1999)

Geoid undulation modelling and interpretation at Ladak, NW Himalaya using GPS and levelling data - P. Banerjee; G. R. Foulger; Not Available Not Available; C. P. Dabral (Journal of Geodesy, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Some aspects of volcanic ash layers in the Central Indian Basin - N. P. Sukumaran; R. Banerjee; D. V. Borole; S. M. Gupta (Geo-Marine Letters, 1998)

Biphasic estrogen response on bovine adrenal medulla capillary endothelial cell adhesion, proliferation and tube formation - Sushanta K. Banerjee; Donald R. Campbell; Allan P. Weston; Dipak K. Banerjee (Molecular and Cellular Biochemistry, 1997)

Panel discussion on “National laboratory network for immuno-diagnostics of infectious diseases (Nalind)” held on September 6,1997. Brief report - Harinath; P. Usha Sarma; G. K. Khuller; Raman K. Roy; Ambika Banerjee; T. Malati; U. Satyanarayana; P. Das; R. B. Narayanan; D. N. Rao; P. Bansal (Indian Journal of Clinical Biochemistry, 1997)

MEM Analysis of Geomagnetic Field Variations Over Narssarssuaq - M. Banerjee; M. K. Singh; Nagendra P. Singh; T. Lal (Pure and Applied Geophysics, 1997)

Production of hairy roots in Aconitum heterophyllum wall. using Agrobacterium rhizogenes - A. Giri; S. Banerjee; P. S. Ahuja; C. C. Giri (In Vitro Cellular & Developmental Biology - Plant, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Hereditary methaemoglobinaemia due to Cytochrome b-5 reductase deficiency—A case report - U. K. Saha; I. Chakraborty; S. Ghosh; P. Banerjee; A. K. Chakrabarti (Indian Journal of Clinical Biochemistry, 1997)

A cell line from the gill tissues of indian cyprinoid Labeo rohita - P. S. Sathe; A. Basu; D. T. Mourya; B. A. Marathe; S. S. Gogate; K. Banerjee (In Vitro Cellular & Developmental Biology - Animal, 1997)

Identification of 45 kD antigen in immune complexes of patients of allergic bronchopulmonary aspergillosis - Taruna Madan; Banani Banerjee; Pravin K. Bhatnagar; Ashok Shah; P. Usha Sarma (Molecular and Cellular Biochemistry, 1997)

Alginate biosynthesis by Pseudomonas aeruginosa: effect of arsenite and other metabolic inhibitors - P. C. Banerjee (Archives of Microbiology, 1986)

Accumulation of fructose 1,6-bisphosphate in mutant cells of mucoid Pseudomonas aeruginosa as an evidence of phosphofructokinase activity - P. C. Banerjee (Archives of Microbiology, 1986)

Experimental haematogenous pyelonephritis in mice with uropathogenic, enteropathogenic and enterotoxigenic - K. Kakar; S. Sharma; P. J. Asnani; C. K. Banerjee; B. K. Sharma (Antonie van Leeuwenhoek, 1986)